JURNALISME ERA BARU (KONVERGENSI MEDIA RADAR JOGJA DALAM MENGHADAPI PERSAINGAN MEDIA) - Titik Wahyuningsih; Abraham Zakky Zulhazmi (UIN Raden Mas Said Surakarta, 2020)
Freedom of the press after the 1998 reform had an impact on increasing the number of mass media in Indonesia. Coupled with the presence of the internet as new media, making media competition increasingly complex. Faced with this phenomenon a number of media began to try to unite information technology, communication and content which is referred to as media convergence. This research is a qualitative research. Research data collection is done by observation, interview and documentation. This research concludes that Radar Jogja implements the concept of continuum convergence. Radar Jogja has carried out four stages of continuum convergence namely cross promotion, cloning, coopetition, and content sharing. While the form of Radar Jogja's media convergence implementation in the face of media competition, is identified as follows (1) optimization of new media, Radar Jogja has succeeded in becoming a technology-literate media as evidenced by its activity on various media platforms. (2) The issue selection strategy, Radar Jogja is able to raise national issues which are then localized according to the conditions on the field. (3) bandling advertising, a strategy to get clients by providing a variety of advertising service choices. (4) coordination, build a solid team and work together to increase loyalty to the company.